Government policy and political economy in relation local food security in Merauke Regency. Issue 1 (1st December 2022) - Jalal, Nur; Syahruddin,; Oja, Hubertus; Purnama, Erwin Nugraha
Abstract: Food instability can occur a food crisis, and because of that, food security is an important factor in creating food system availability. Local food security is the most important in supporting national food security, while the national food demand has not been fulfilled. The research purpose is to analyze the government policy and politics of the economy in relation to food security by using a descriptive approach. The data interpretation technique is in the form of observation concerning the empirical condition that has happened in reality and is close to literature research. The data analysis uses data reduction, data presentation, verification, and data conclusion. The result shows that the local government policy of Merauke Regency in supporting food security through local food has not been optimum yet. For the production aspect in the early planting to the post-harvesting, the society executes it based on their experiences and tradition. Definitely, the result doesn't mean maximum, although there is training that has been offered to them, but it doesn't have continuity and the lack of assist system. For the trade aspect, the government has not set a market that is available to market the society's products whereas as far as long the society only marketing their products locally. For the cultivation, aspect is not maximum yet with the exploiting of the slumber land to cultivate of local plants for production process continually. Because of that, it is necessary to have a supporting policy, which is integrated and supported by the political economy as a national area or regional area to support food security.